TLR3 agonists induce fibronectin aggregation by activated astrocytes: a role of pro-inflammatory cytokines and fibronectin splice variants - Werkman, Inge (Sci Rep, 2020)
Multiple sclerosis (MS) is a chronic demyelinating disease of the central nervous system which eventually results in axonal loss mainly due to failure of remyelination. Previously we have shown that the persistent presence of stable astrocyte-derived fibronectin aggregates in MS lesions impairs OPC differentiation, and thereby remyelination. Here we set out to discern whether and, if so, how inflammatory mediators as present in MS lesions trigger astrocytes to form fibronectin aggregates. Our findings revealed that in slice cultures only upon demyelination, the TLR3 agonist Poly(I:C) evoked astrocytes to form fibronectin aggregates. Consistently, pro-inflammatory cytokine-pretreated astrocytes were more susceptible to Poly(I:C)-induced fibronectin aggregation, indicating that astrocytes form fibronectin aggregates upon a double hit by inflammatory mediators. The underlying mechanism involves disrupted fibronectin fibrillogenesis at the cell surface as a result of a cytokine-induced increase in relative mRNA levels of EIIIA(pos)-Fn over EIIIB(pos)-Fn and a Poly(I:C)-mediated decrease in integrin affinity. Remarkably, fibronectin aggregation is exacerbated by white matter astrocytes compared to grey matter astrocytes, which may be a reflection of higher expression levels of EIIIA(pos)-fibronectin in white matter astrocytes. Hence, interfering with alternative fibronectin splicing and/or TLR3-mediated signaling may prevent fibronectin aggregation and overcome remyelination failure in MS lesions.